Kontribusi Sektor Kehutanan Terhadap Pendapatan Asli Daerah Pada Era Otonomi Daerah di Kabupaten Muna - A Mujetahid M A Mujetahid M (Biocelebes, 2009)
This research was aimed to know contribution of forestry sector to Local Government Revenue (Pendapatan Asli Daerah, PAD) at district of Muna in regional autonomy era. The research result is expected to contribute in evaluating and compiling Regional Budget and Expenditure Plan. The result is also intended as an evaluation of forest product restribution policy. This research was carried out in Muna district. Data collected with purpossive sampling using observation technique/survey, interview and discussion with related stakeholders. The data than processed, tabulated and clasified base on with research aim, and analysed descriptively. The results show that the contribution of forestry sector to PAD to Muna district during 2000-2004 in average was 38,88% of PAD in total.